With books and bricks : how Booker T. Washington built a school - Slade, Suzanne (Albert Whitman & Company, 2014)
"Booker T. Washington had an incredible passion for learning. Born a slave, he taught himself to read. When the Civil War ended, Booker finally fulfilled his dream of attending school. After graduation, he was invited to teach in Tuskegee, Alabama. Finding many eager students, but no school, Booker set out to build his own school--brick by brick"--